Preparation and characterization of coconut shell liquid smoke and the properties of preserving tofu - Gani A.; Adlim M.; Rahmayani R.F.I. (Kuwait Journal of Science)
Coconut shell waste can generate environmental problems if left without treatment, as it contains lignin, cellulose, and hemicellulose compounds, which pyrolyze to produce liquid smoke, charcoal, and tar. This study aims to prepare and characterize liquid smoke using several parameters, including the chemical content preserving tofu and the hedonic test of consumer preferences. The dried coconut shell (3000 g) was pyrolyzed at 300 °C for 5 h. Liquid smoke (grade 3) was purified by distillation (grade 2) and filtered with activated charcoal to produce grade 1 liquid smoke. The liquid smoke properties were characterized as yield, pH, phenol, and moisture, while the chemical components were identified by gas chromatography-mass spectroscopy (GC-MS). For the commercial and coconut shell liquid smoke (grade 1) used in this study, the application was aimed at preserving the tofu for three days. Panelists observed the aroma, the texture, and the appearance compared to the control. Ten panelists performed the hedonic test of fried preserved tofu. The organoleptic aspects included taste, texture, aroma, and color. The liquid smoke obtained from coconut shell pyrolysis was red-brown, with a yield of 52.75%, pH 0.5 (grade 3), pH 1.7 (grade 2), and pH 2.3, with a total phenol of 2.479 (grade 1). The GC-MS results exhibited three essential chemical compounds, namely phenol, methoxy phenol, and hydroxyphenyl phosphonic acid, influencing the preservation. The liquid smoke solution extended the shelf life of tofu, especially at a concentration of 1.5 (% v/v), so the water content decreased. The average panelist responded “good” on the hedonic test on all of the tofu treatments compared to the control. © 2024 The Authors